1990
DOI: 10.1111/j.1365-2923.1990.tb02509.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse learning strategy: the Adelaide Diagnostic Learning Inventory and its subscale replicability in a medical student population

Abstract: The Adelaide Diagnostic Learning Inventory (ADLIMS) is a measure of learning styles and learning pathologies that was designed to investigate the impact of traditional approaches to learning versus problem-based learning and to identify students whose approach to learning tasks predicted poor academic performance. In this study, some important psychometric properties of the ADLIMS were examined, including its factor structure. In this study, factor replicability across samples was argued to provide a more robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 8 publications
5
18
0
Order By: Relevance
“…While the present study was able to replicate the dimensionality of the ADLI, as suggested by Welch et at. (1990) in a known multicultural sample, it also indicated that Asian medical students in Australia may experience greater levels of difficulty in achieving their learning objectives.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…While the present study was able to replicate the dimensionality of the ADLI, as suggested by Welch et at. (1990) in a known multicultural sample, it also indicated that Asian medical students in Australia may experience greater levels of difficulty in achieving their learning objectives.…”
Section: Discussionsupporting
confidence: 69%
“…For this reason the intercorrelation matrix among the ADLI items was subjected to principal components analysis with orthogonal rotation to aid interpretation of the main axes. Table 4 shows the resulting three factor structure together with the solution obtained by Welch et al (1990). In the lower part of Table 4 Harman's Congruence Coefficients (Harman 1960) indicate the similarity between the Welch et al (1990) solution and the solution obtained here.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations